Conjugated linoleic acid and fatty acid binding protein as antioxidants - Piergiacomi, V.A. (2006)
Studies were carried out to determine the effect of conjugated linoleic acid (CLA) and rat liver cytosolic protein enriched in fatty acid binding protein (FABP) on the non-enzymatic lipid peroxidation of rat liver microsomes. The inhibition of lipid peroxidation was more evident when the FABP containing fraction obtained from CLA-group was used with either kind of microsomes (CLA and control). The chemiluminescence and polyunsaturated fatty acid composition of rat liver microsomes changed after CLA treatment. When native and peroxidized microsomes obtained from control group were compared, the most affected polyunsaturated fatty acids were: C18:2, C18:3 and C20:4, while in CLA-group C20:4 was mainly peroxidized The simultaneous analysis of chemiluminescence and fatty acid composition demonstrated that CLA and FABP play a role protecting rat liver microsomes against the harmful effect of lipid peroxidation.